Vergi Uyuşmazlıklarının İdari ve Adli Yargı Kapsamında Çözüm Süreçleri ve Önerileri - Yegen, Baki (Muş Alparslan Üniversitesi, 2019)
About the taxation relationship disputes areexperienced from time to time between tax creditor state with the debtorindividual. The dispute is referred as tax disputes in the literature. Taxdisputes may be about the amount of payable tax which is calculated by theadministration or may be about the penalties which are as a result of taxpayersact contrary to the laws of tax. Penalties is given according to the type ofaction by the administration or by the judicial authority. The taxpayers areentitled applying to legal means about the disputes which are including thepenalties. In this context, although taxpayers can follow the similar ways, judicial bodies and the solution processes can vary.

Vergi alacaklısı olan devlet ile borçlu konumunda olan birey arasında vergilemeilişkisi ile ilgili olarak zaman zaman anlaşmazlıklar yaşanmaktadır. Söz konusuanlaşmazlıklar literatürde vergi uyuşmazlığı olarak ifade edilmektedir. Vergiuyuşmazlıkları idare tarafından hesaplanan ödenecek vergi miktarı konusundaolabileceği gibi mükelleflerin vergi kanunlarına aykırı hareket etmelerineticesinde aldıkları cezalar konusunda da olabilmektedir. Cezalar eylemtürlerine göre idare tarafından ya da adli merci tarafından verilmektedir.Verilen cezalarla ilgili yaşanan uyuşmazlıklarda mükelleflere kanun yollarınagidebilme hakkı tanınmaktadır. Bu kapsamda mükelleflerin takip edebileceklerikanun yolları benzerlik göstermesine rağmen yargı organları ve çözüm süreçlerifarklılık göstermektedir.
The Solution Process and Suggestions of Tax Disputes within the Scope of Administrative and Judicial Jurisdiction
anemon
Keywords: Tax Disputes; Administrative Judiciary; Judicial Judiciary; Adli Yargı; İdari Yargı; Vergi Uyuşmazlıkları